Implementasi desain sistem website ray catfish palembang dengan metode atomic design - Pratama, Rendy Almaheri Adhi; Putri, Meidyan Permata; Hermawan, Ade; Gustiana, Mega Anita; Gunawan, Raynanda (MDP Student Conference, 2024)
A web-based application can help business managers manage inventory, track customer orders, and optimize business processes including sales and marketing. Currently, the process of buying and selling catfish fry at RAY Catfish Palembang is still simple, namely recorded in the sales transaction book. This can lead to a number of difficulties such as difficulty in recording the number of stocks, time-consuming ordering process, both recording orders, checking the available fry stocks, and irregular reporting. The software development method used in this study is the Waterfall method as the system design method. Then the Atomic Design concept will be applied in the design of the system design. A good website system design can provide optimal user experience. Atomic Design is a design methodology consisting of five stages that work together to create a hierarchical user interface design system, starting from atoms, molecules, organisms, templates, to pages. The use of repetitive components can produce efficient and consistent designs. With the presence of a web-based freshwater fish fry sales application, it can facilitate RAY Catfish Palembang managers in tracking inventory and sales, as well as increasing efficiency in ordering and selling catfish fry.